Didactic Strategies to Improve Emotional Intelligence in Nursing Students - Nely Yolanda Silva Fernández; Elena Vega Torres; Yudelly Torrejón Rodríguez; Urfiles Bustamante Quiroz; Leyder Guerrero Quiñones (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigated the influence of a program of socioformative didactic strategies in the improvement of emotional intelligence of students of the VII cycle of semester 2021-I, of the Academic Professional School of Nursing of the National University of Cajamarca, Jaén Branch. The study used a quantitative, explanatory and pre-experimental design with pre-test and post-test. The study population consisted of 172 students, of which 120 formed the experimental group. The Socioformative Didactic Strategies Program was applied to improve emotional intelligence. Observation techniques and BarOn's Inventory of Emotional Intelligence (I-CE) adapted by Ugarriza were applied. The results showed significant improvements in students' emotional competencies, especially in empathy, interpersonal relationships and stress management. Although the Wilcoxon test did not reveal statistically significant differences between pre-test and post-test, qualitative observations suggest a positive impact of the program on students' emotional development. In conclusion, the implementation of socioformative didactic strategies significantly improved the emotional competencies of nursing students, underscoring the importance of integrating emotional intelligence development programs into the nursing curriculum to improve students' personal and professional well-being and better prepare them for the challenges of their future professional practice.